Oxalate Carbonate Pathway—Conversion and Fixation of Soil Carbon—A Potential Scenario for Sustainability - Syed, Shameer; Buddolla, Viswanath; Lian, Bin (Frontiers in Plant Science, 2020)
It is still an important aspect of global climate research to explore a low-cost method that can effectively reduce the increase of CO2 concentration in the global atmosphere. Oxalotrophic bacterial communities exist in agricultural or forest soil with ubiquitous oxalate as the only carbon and energy source. When soil oxalate is oxidized and degraded, carbonate is formed along with it. This process is called the oxalate carbonate pathway (OCP), which can increase soil inorganic carbon sink and soil organic matter content. This soil carbon sink is a natural CO2 trapping system and an important alternative if it is properly managed for artificial sequestration/ storage. As the main driver of OCP, the oxalate degrading bacteria are affected by many factors during the oxalate conversion process. Understanding this process and the synergy of oxalogenic plants, saprophytic decomposers, and oxalotrophic bacteria in agricultural or forest soil is critical to exploiting this natural carbon capture process. This article aims to provide a broader perspective of OCP in CO2 sequestration, biomineralization, and elemental cycling.